Jak są zrobione wykłady Norwida o Słowackim - Buś, Marek (Colloquia Litteraria, 2019)
The article is interested in exploring the peculiarities and proper organiza- tion of Cyprian Norwid’s O Juliuszu Słowackim. The author analyzes cha- racteristics of the text such as its structure, internal links between elements, dynamics, and stylistic features; he focuses on their functions, which are considered manifestations of larger ideas and goals of the author, his psy- chological, or even psychophysical, traits. The article pays special attention to such issues as the text’s cohesion, the elaboration of the main theme of the work - the exposition of Słowacki’s oeuvre, or better say, expression of his own critical method/attitude - communication relationships advanced by Norwid (sender-receiver), reception styles (image of the reader), and forms of the objectification of views.